Poverty Management through the Empowerment of Productive Asnaf: Exploring the Effectiveness of Micro-Credit Assistance in Indonesia to Achieve SDG 1 - Ebekozien, Andrew; Ahmed, Mohamed Ahmed Hafez; Ghazali, Nooramira Binta; Samsurijan, Mohamad Shaharudin; Hamat, Zahri; Nizam, Ahmad Nizam Ahmad (Journal of Posthumanism, 2025)
The micro-credit programme is a medium for distributing zakat to productive and non-productive asnaf. Studies regarding the effectiveness of micro-credit distributed to productive asnaf in Baitul Mal Aceh (BMA) are scarce, especially in Indonesia. Moreover, there is a paucity of literature on how productive asnaf utilise their micro-credit to grow their businesses and enterprises. Thus, using a case study, this study investigated the effectiveness of micro-credit assistance given to productive Indonesia’s Asnaf to achieve Sustainable Development Goal 1 (SDG 1) and how they grow their businesses and enterprises through a qualitative approach. Data were collected through unstructured interviews involving 12 participants and analysed using the content analysis method of the thematic approach. The findings show that distributed micro-credit assistance has helped productive asnaf accommodate and boost their businesses and enterprises. Indirectly, the BMA has produced a productive group of asnaf who successfully increased their family income and reduced the problem of poverty. This study is one of the few to develop a model for poverty relief programmes in Indonesia. The BMA needs to improve the quality of poverty management programmes, especially for productive asnaf, in the future, via all-inclusive engagement and integrated collaboration.